FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA DAN KETERSEDIAAN BERAS DI TINGKAT NASIONAL - Widodo Widodo (Universitas Sebelas Maret, 2014)
The objectives of this study were: (1) to understand the development of domestic rice prices at the national level, (2) to identify factors that influence the domestic rice prices at the national level, and (3) to determine the factors that affect the availability of rice at the national level. The data used in this research was secondary data obtained from the BPS, BULOG, and FAO statistics. The data obtained were systematically recording in the form of a time series data since 1979 until 2008 at the national level. The model used in this research is simple regression equation or the Ordinary Least Square (OLS). This model was used to identify trends and the factors affecting the price and availability of rice nationwide. Regression equations estimated to test the functionality of R2, the F-test, t-test, and D-W.The results of this study indicate: (1) the rate of growth of retail rice prices at the national level has increased in the positive trend, (2) the domestic rice prices at the national level is influenced by the base price of grain and world rice prices, and (3) the availability of long-term national from the year 1979-2008 rice prices was influenced by domestic supply, exchange rate farmers, the harvested area, and the availability of rice before and after the moneter crisis. The availability of rice in the short term before and after the crisis were influenced significantly by harvested area, at the time of pre-crisis (1979-1997) and by domestic supply, farmers exchange rate, and the harvested area, on the time after the crisis (1997-2008).